2022
DOI: 10.1007/s10644-022-09434-z
|View full text |Cite
|
Sign up to set email alerts
|

Does political risk undermine environment and economic development in Pakistan? Empirical evidence from China–Pakistan economic corridor

Abstract: China–Pakistan Economic Corridor (CPEC) invests billion in Pakistan’s energy, infrastructure, and other development projects to step toward Eurasia’s economic integration. However, CPEC may exacerbate climate change vulnerabilities for Pakistan’s struggling economy due to potential environmental hazards and consequences. In this context, the current study seeks to examine the impact of political risk on carbon emissions and economic growth in Pakistan while also considering the relevance of trade o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 95 publications
2
6
0
Order By: Relevance
“…However, the irregularity of these revolutionary changes has resulted in an unsustainable institutional environment. Pakistan's agricultural performance and environmental quality are falling daily because of the country's weak IQ; consequently, appropriate institutional improvements are essential (Ashraf, 2022b; Hassan et al, 2020).…”
Section: Methodology and Datamentioning
confidence: 99%
See 2 more Smart Citations
“…However, the irregularity of these revolutionary changes has resulted in an unsustainable institutional environment. Pakistan's agricultural performance and environmental quality are falling daily because of the country's weak IQ; consequently, appropriate institutional improvements are essential (Ashraf, 2022b; Hassan et al, 2020).…”
Section: Methodology and Datamentioning
confidence: 99%
“…To ensure the variables in our CO 2 model are not mutually cointegrated, we ran the cointegration test proposed by Phillips and Ouliaris (1990). This method depends on residuals, and its power attributes are increased when testing for cointegration in small datasets (Ashraf, 2022b; Haug, 1992). The NH states that the factors that do not make up a cointegrating vector under the Žα test are evaluated using the multivariate Phillips–Ouliaris approach (Haug, 1992).…”
Section: Methodology and Datamentioning
confidence: 99%
See 1 more Smart Citation
“…For the past three decades, a great deal of research has looked at the relationship between political risk and CO 2 emissions, but its conclusions have been mixed. For instance, using the autoregressive distributed lag (ARDL) approach, Ashraf (2023) discovered that a more favorable political climate (lower political risk) encourages economic development and reduces carbon emissions in Pakistan over the period 2000–2020. Using the ARDL method, van Vu and Huang (2020) studied the effect of political risk on CO 2 emissions in Vietnam.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Islam and Shindaini (2022) found a similar result in Bangladesh. Recently, Ashraf (2023), using the ARDL bound test, revealed that political stability plays a key role in enhancing economic growth in Pakistan. In a cross-country study of Belt and Road Initiative countries, Ashraf (2022) assessed the impact of political instability on economic complexity.…”
Section: Introductionmentioning
confidence: 99%